2005
DOI: 10.1126/science.1104054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Formation of Sulfuric Acid Particles at Near-Atmospheric Conditions

Abstract: We investigated the formation of new particles in a laboratory study, starting from H2SO4 produced in situ through the reaction of OH radicals with SO2. Newly formed particles were observed for H2SO4 concentrations above 7 x 10(6) per cubic centimeter. At 293 kelvin, a rough estimate yielded a nucleation rate of 0.3 to 0.4 particles per cubic centimeter per second for approximately 10(7) particles per cubic centimeter of H2SO4 (particle size >/= 3 nanometers). These findings are in agreement with observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
224
5
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(254 citation statements)
references
References 33 publications
23
224
5
2
Order By: Relevance
“…We compared our results to previous experiments of α-pinene ozonolysis conducted in the Tropos Laminar Flow Tube (Berndt et al, 2005) and the…”
Section: Methodssupporting
confidence: 55%
“…We compared our results to previous experiments of α-pinene ozonolysis conducted in the Tropos Laminar Flow Tube (Berndt et al, 2005) and the…”
Section: Methodssupporting
confidence: 55%
“…On the other hand, recent laboratory experiments showed that at atmospheric pressure, 288 K and 10-55% RH, the threshold [H 2 SO 4 ] needed for unit J value is in the range of 10 8 -10 9 cm −3 and the measured J was proportional to [H 2 SO 4 ] with the second to tenth powers [Benson et al, 2008]. Other laboratory studies, on the other hand, showed that nucleation takes place at lower [H 2 SO 4 ] concentration [Berndt et al, 2005] and with J proportional to [H 2 SO 4 ] to the first to second power [Metzger et al, 2010] (Figure 7c). This may indicate that NH 3 effects on aerosol nucleation are already saturated at this measured [NH 3 ] (sub-ppbv), as predicted from modeling studies [Merikanto et al, 2007].…”
Section: H 2 So 4 Effects On Nucleationmentioning
confidence: 99%
“…OH radicals were produced from UV dissociation of water vapor; this allows for an ozone-free system and hence provides an advantage compared to other studies where OH was produced from ozone photolysis (Berndt et al, 2005(Berndt et al, , 2006Sipilä et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…These newly formed particles further grow by condensation and coagulation and can contribute to a large fraction (15-55 %) of CCN concentrations at the global scale (Merikanto, 2009), but the nucleation mechanisms are not well understood. Atmospheric observations (Erupe et al, 2010;Kulmala et al, 2004;McMurry et al, 2005) and laboratory studies Berndt et al, 2005;Sipilä et al, 2010; have shown that sulfuric acid (H 2 SO 4 ) is the main nucleation precursor, but the role of other ternary species such as ammonia (NH 3 ) and organic compounds is not well understood.…”
Section: Introductionmentioning
confidence: 99%